THE IMPACT OF CONSUMER REVIEW ON PURCHASE INTENTION OF INTERNET / TELEPHONE SERVICE PROVIDER IN MANADO - Limpong, Estela Isabelita Evita; Kindangen, Paulus; Tumbuan, Willem J.F.A (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
At this time, internet / telephone service providers have an important role in all aspects of everyone's life, when every activity such as work and education must be carried out from home because of the Covid  19 disease, internet / telephone services become a priority need today. Internet / telephone service providers provide a lot of convenience to communicate for each user, and provide quality connection stability which greatly affects every consumer in their purchase intention. The objectives of this research is to know the impact of consumer review on purchase intention of internet / telephone service provider in Manado. The population in this research refers to the general consumer of internet / telephone service provider in Manado. Finding of this research shows that the consumer  reviews have an impact on purchase intention of internet / telephone service provider products, indeed  not all consumers prioritize reviews from other consumers before making a purchase, but most of them  tend to look at the reviews from other consumers when they want to purchase internet / telephone service  provider products.  Keywords: Consumer Review, Purchase Intention